A magyarországi gyógy- és termálturizmus fejlesztésének néhány területi aspektusa - Bakucz, Márta; Flink, Alexandra (Jelenkori Társadalmi és Gazdasági Folyamatok, 2012)
In East Central Europe, and especially in Hungary, the increasing importance of the Medicinal and Thermal sector of Spa Tourism is beyond dispute. The selected basis for our research is South Transdanubia. This Region has truly outstanding natural potential in the sector, but the results of investment and development over recent years have not matched expectations. An analysis of statistical data revealed a gradual decrease in demand and the resulting falling behind of the region. Within the framework of our empirical research to date a total of ten spas (both medicinal and thermal) in Southern Transdanubia have been surveyed, in an attempt to identify reasons why visitors are staying away from the region. These embraced a lack of quality accommodation, the absence of a unified concept for the regional development of the sector and also of ’co-opetition’. Finally, through the ’best practice’ example of the Burgenland, an Austrian province with similar potential we have indicated further problems.